Trends in Cleft Lip and Palate Surgery: A Half-Century Bibliometric Analysis and Literature Review - Rahman, Naufal A.; Devina, Santi; Diani, Masyithoh W. (International Journal of Medical Science and Clinical Research Studies, 2024)
Introduction: Cleft lip and palate (CLP) are significant congenital anomalies requiring comprehensive surgical and multidisciplinary care. This study conducts a bibliometric analysis CLP surgery research to identify key authors, topics, and journals, highlighting collaboration trends and providing insights into current research and future directions. Methods: The data was acquired online from Scopus on May 22nd, 2024 with a search spanning from 1974 to 2024, yielding 7,283 relevant documents. The publication output was then analyzed using VOSViewer to provide the visual representation. Results and Discussion: The results indicate an increase in research studies over the years. Lo, L.J. emerged as the top researcher, with the United States leading in research output. Researchers primarily focused on three areas: surgical techniques, complications, and secondary procedures. Emerging areas such as patient quality of life, velopharyngeal insufficiency, and nonsyndromic clefting are gaining interest for future research. Conclusion: Significant progress in CLP surgery has improved patient outcomes and quality of life over the past fifty years. Continued research and international collaboration are essential to address global disparities and ensure equitable access to advanced CLP care, further enhancing outcomes and quality of life for all patients.